Learning JavaScript Design Patterns : a JavaScript and React developer's guide - Osmani, Addy (O'Reilly Media, 2023)
Do you want to write beautiful, structured, and maintainable JavaScript by applying modern design patterns to the language? Do you want clean, efficient, manageable code? Want to stay up-to-date with the latest best practices? If so, the updated second edition of Learning JavaScript Design Patterns is the ideal place to start. Author Addy Osmani shows you how to apply modern design patterns to JavaScript and React--including modules, mixins, observers, and mediators. You'll learn about performance and rendering patterns such as server-side rendering and Islands architecture. You'll also learn how architectural patterns like MVC, MVP, and MVVM are useful from the perspective of a modern web application developer. This book explores: Architectural patterns for structuring your components and apps More than 20 design patterns in JavaScript and React, applicable for developers at any level Different pattern categories including creational, structural, and behavioral Essential performance patterns including dynamic imports and code-splitting Rendering patterns such as server-side rendering, hydration, Islands architecture, and more Additionally, you'll explore modern JavaScript syntax like JavaScript modules, React patterns like Hooks, higher-order components (HOCs), and more, to stay ahead in the ever-evolving world of web development.